Biomechanical Evaluation of Oblique Lumbar Interbody Fusion with Various Fixation Options: A Finite Element Analysis. Issue 2 (22nd February 2021) - Song, Chengjie; Chang, Hengrui; Zhang, Di; Zhang, Yingze; Shi, Mingxin; Meng, Xianzhong
Abstract : Objective: The aim of the present study was to clarify the biomechanical properties of oblique lumbar interbody fusion (OLIF) using different fixation methods in normal and osteoporosis spines. Methods: Normal and osteoporosis intact finite element models of L1 –S1 were established based on CT images of a healthy male volunteer. Group A was the normal models and group B was the osteoporosis model. Each group included four subgroups: (i) intact; (ii) stand‐alone cage (Cage); (iii) cage with lateral plate and two lateral screws (LP); and (iv) cage with bilateral pedicle screws and rods (BPSR). The L3 –L4 level was defined as the surgical segment. After validating the normal intact model, compressive load of 400 N and torsional moment of 10 Nm were applied to the superior surface of L2 to simulate flexion, extension, left bending, right bending, left rotation, and right rotation motions. Surgical segmental range of motion (ROM), cage stress, endplate stress, supplemental fixation stress, and stress distribution were analyzed in each group. Results: Cage provided the minimal reduction of ROM among all motions (normal, 82.30%–98.81%; osteoporosis, 92.04%–97.29% of intact model). BPSR demonstrated the maximum reduction of ROM (normal, 43.94%–61.13%; osteoporosis, 45.61%–62.27% of intact model). The ROM of LP was between that of Cage and BPSR (normal, 63.25%–79.72%; osteoporosis, 70%–87.15% of intact model). Cage had the minimal cage stress and endplate stress. With the help of LP and BPSR fixation, cage stress and endplate stress were significantly reduced in all motions, both in normal and osteoporosis finite element models. However, BPSR had more advantages. For cage stress, BPSR was at least 75.73% less than that of Cage in the normal model, and it was at least 80.10% less than that of Cage in the osteoporosis model. For endplate stress, BPSR was at least 75.98% less than that of Cage in the normal model, and it was at least 78.06% less than that of Cage in the osteoporosis model. For supplemental fixation stress, BPSR and LP were much less than the yield strength in all motions in the two groups. In addition, the comparison between the two groups showed that the ROM, cage stress, endplate stress, and supplemental fixation stress in the normal model were less than in the osteoporosis model when using the same fixation option of OLIF. Conclusion: Oblique lumbar interbody fusion with BPSR provided the best biomechanical stability both in normal and osteoporosis spines. The biomechanical properties of the normal spine were better than those of the osteoporosis spine when using the same fixation option of OLIF. Abstract : In this study, we established OLIF finite element models with various fixation options in normal and osteoporosis spines, and found that OLIF with BPSR fixation had the best biomechanical properties.